Status Kualitas Air dan Kesuburan Perairan Waduk PLTA Koto Panjang, Provinsi Riau - Ika Fitria Hasibuan; Sigid Hariyadi; Enan Mulyana Adiwilaga (Jurnal Ilmu Pertanian Indonesia, 2017)
PLTA Koto Panjang Reservoir is one of the reservoirs in Riau Province which has a primary function as a Hydropower source and also used for fisheries and tourism activities. Increased activity around the existing reservoir affecting water quality conditions that would interfere with function.This research was conducted in April-May 2015 with three observations on 5 stations with the aimed this research to analyzing, determining the status of water quality, and fertility status of waters in PLTA Koto Panjang Reservoir. Determination of reservoir water quality status based on parameters of physical, chemical, and biological methods STORET with water quality standard Class II and III for comparison. Fertility status was determined by Trophic Level Index (TLI) based on the brightness, chlorophyll-a, total nitrogen, and total phosphorus waters. The results showed that the status of Koto Panjang Reservoir water quality can be categorized as being contaminated with the quality standard Class III and heavily polluted the quality standard Class II. The parameters have exceeded the water quality standard Class II and III are ammonia, nitrite, and BOD5. The fertility status of the dam water is the eutrophic category with TLI values ranges from 4.6-5.2.